PRELIMINARY ASSESSMENT OF DISSOLVED AND PARTICULATE HEAVY METALS TRANSPORTED BY THE RED RIVER AT THE SONTAY STATION - Ha, Dang Thi; Coynel, Alexandra (Vietnam Journal of Earth Sciences, 2014)
This study is based on the experimental results obtained from analysis of suspended and dissolved heavy metal concentrations (V, Cr, Co, Ni, Cu, Zn, As, Mo, Cd, Sb, Pb and Th) in the Red River at the SonTay station during 2011. The results showed that for the dissolved phase, heavy metal concentrations were relatively stable, whatever the water discharges. In contrast, the concentration of suspended heavy metals tended to decrease with increasing of water discharge. Moreover, the results indicated also that the transfert of heavy metals by the Red River was mainly in the suspended phase (up to 99 %). If the water quality of the Red River can be classified as good (column A - QCVN08: 2008/BTNMT) in term of dissolved heavy metal concentrations; the suspended heavy metal concentrations were higher than the ecological indicators PEC (Probable Effect Concentration), suggesting the effect of this heavy metal contamination on the ecology and environment in the Red River basin is extremely high (over 50% ). Finally, this study estimated the contribution of the Red River on the global flux from 0.1 to 0.4% for dissolved phase and from 0.4% to 2.2 for suspended phase. References Berg M., Stengel C., Trang P.T.K., Pham H.V., Sampton M.L., and Leng M., 2007. Magnitude of arsenic pollution in the Mékong and Red River Deltas-Cambodia and Vietnam, Science of the Total Environment 327, 413-425. Blake, W.H., Walsh, R.P.D., Barnsley, M.J., Palmer, G., Dyrynda, P., James, J.G., 2003. Heavy metal concentrations during storm events in a rehabilitated catchment. Hydrol. Process. 17, 1923-1939. Cenci R.M., and Martin J.M., 2004. Concentration and fate of trace metals in Mekong River Delta. Science of the total Environment 332, 167-182. Coynel A., Schafer J., Blanc G., and Bossy C., 2007. Scenario of particulate trace metal and metalloid transport during a major flood event inferred from transient geochemical signals. Applied Geochemistry 22, 821-836. Coynel A., Blanc G., Marache A., Schäfer J., Dabrin A., Maneux E., Bossy C., Masson M., and Lavaux J. 2009. Assessment of metal contamination in a small mining- and smelting-affected watershed: high resolution monitoring coupled with spatial analysis by GIS, J Environ Monit. 11, 962-976. Dang T.H., Coynel A., Orange D., Blanc G., Etcheber H., and Le L.A., 2010. Long-term monitoring (1960-2008) of the river-sediment transport in the Red River Watershed (Vietnam): temporal variability and dam-reservoir impact, Science of the Total Environment 408, 4654-4664. Dang T.H., Coynel A., 2013. Assessment of arsenic contamination in the Red River: high resolution monitoring coupled with spatial analysis by GIS. Journal of Sciences and Technology, 51, 779-788. Eiche E., Neumann T., Berg M., Weinman B., van Geen A., Norra S., Berner Z., Stüben, D., 2008. Geochemical processes underlying a sharp contrast in groundwater arsenic concentrations in a village on the Red River delta, Vietnam. Applied Geochemistry 23, 3143-3154. Horowitz A.J., Meybeck M., Idlafkih Z., and Biger E., 1999. Variations in trace element geochemistry in the Seine River Basin based on floodplain deposits and bed sediments, Hydrological Processes 13, 1329-1340. Horowitz AJ, Elrick KA, Smith JJ., 2001. Annual suspended sediment and trace element fluxes in the Mississippi, Columbia, Colorado, and Rio Grande drainage basins. Hydrolog Process 15, 1169-1207. Huang X., Sillanpa M., Duo B. and Gjessing ET., 2008. Water quality in the Tibetan Plateau: Metal contents of four selected rivers. Environmental Pollution 156, 270-277. MacDonald DD., CG. Ingersoll, TA. Berger., 2000. Development and Evaluation of Consensus-Based Sediment Quality Guidelines for Freshwater Ecosystems. Arch. Environ. Contam. Toxicol. 39, 20-31. Masson M., 2007. Sources et transferts métalliques dans le basin versant de la Gironde-Réactivité et mécanismes géochimiques dans l’estuaire fluvial de la Gironde. Thèse doctorat de l’Université Bordeaux 1, 344 pp. Meybeck M., 1998. Man and river interface multiple impacts on water and particulates chemistry illustrated in the Seine River Basin, Hydrobiologia 373, 1-20. Osman, A.E. and Maha, A.A., 2005. Contribution of some trace elements from an Egyptian huge drain to the Mediterranean sea, west of Alexandria. Egypetian journal of aquatic research 31, 120-129. Schäfer J. , G. Blanc, S. Audry, D. Cossa C. Bossy., 2006. Mercury in the Lot-Garonne River system (France): Sources, ﬂuxes and anthropogenic component. Applied Geochemistry 21, 515-527. Singh P., 2010. Geochemistry and provenance of stream sediments of the Ganga River and its major tributaries in the Himalayan region, India. Chemical Geology 269, 220-236. Taylor, S.R., McLennan, S.M., 1985. The Continental Crust: Its Composition and Evolution. Blackwell, Oxford, 312 pp. Viers J., Dupréa B., and Gaillardet J., 2009. Chemical composition of suspended sediments in World Rivers: New insights from a new database. Science of the total environment 407, 853-868. Zhang J., W.W. Huang, R. Letolle, C. Jusserand, 1995. Major element chemistry of the Huanghe (Yellow River), China - weathering processes and chemical fluxes. Journal of Hydrology 168, 173-203.